2009
DOI: 10.1631/jzus.b0820133
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenosides stimulated the proliferation of mouse spermatogonia involving activation of protein kinase C

Abstract: Abstract:The effect of ginsenosides on proliferation of type A spermatogonia was investigated in 7-day-old mice. Spermatogonia were characterized by c-kit expression and cell proliferation was assessed by immunocytochemical demonstration of proliferating cell nuclear antigen (PCNA). After 72-h culture, Sertoli cells formed a confluent monolayer to which numerous spermatogonial colonies attached. Spermatogonia were positive for c-kit staining and showed high proliferating activity by PCNA expression. Ginsenosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Combined administration of PMA and FSH resulted in a visible increase in the germ cell number and LI. These conclusions were consistent with the viewpoints that the treatment of ovarian germ cells and mouse spermatogonia with PMA and ginsenosides promoted the cell proliferation involving the PKC-mediated system Zhang et al, 2009). Hence, we propose that PKCmediated system is involved in the FSH-stimulated cell proliferation in cultured chicken ovarian germ cells.…”
Section: Discussionsupporting
confidence: 92%
“…Combined administration of PMA and FSH resulted in a visible increase in the germ cell number and LI. These conclusions were consistent with the viewpoints that the treatment of ovarian germ cells and mouse spermatogonia with PMA and ginsenosides promoted the cell proliferation involving the PKC-mediated system Zhang et al, 2009). Hence, we propose that PKCmediated system is involved in the FSH-stimulated cell proliferation in cultured chicken ovarian germ cells.…”
Section: Discussionsupporting
confidence: 92%
“…Ginsenosides are the primary components of ginseng and positively affect reproductive organs and other tissues [20,22]. The supplementation of WG at WG2 in the current study improved FCR, HDEP, AEW, EM, TNF-, yolk ginsenoside content, and microflora DNA in the last phase of our experiment but had no positive effect on ADFI, BW, and egg quality.…”
Section: Discussionmentioning
confidence: 44%
“…GS are the main molecular components responsible for the actions of ginseng and exert varying effects on a myriad of cells and tissues. Literature reports suggest that GS could play a positive role in reproduction (Salvati et al, 1996; Kang et al, 2002; Yu et al, 2003; Zhang et al, 2009). Our laboratory reported that GS stimulate murine oocyte meiotic maturation indirectly via the cumulus cells.…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al (2002) reported that ginseng intestinal metabolite‐I reduced doxorubicin toxicity in the mouse testis. Furthermore, a previous study had demonstrated the direct proproliferating effect of GS on mouse spermatogonia and chicken primordial germ cells through PKC (protein kinase C) activation (Ge et al, 2007; Zhang et al, 2009). In females, GS could ameliorate ovarian dysfunction that was caused by excessive stimulation by equine chorionic gonadotropin in immature rats (Yu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%